Decreased small mammals species diversity and increased population abundance along a gradient of agricultural intensification - GENTILI, Stefania; SIGURA, Maurizia; Bonesi, Laura (2014)
Agricultural intensification has been widespread worldwide over the last decades and has lead to a loss of semi-natural habitats. These changes are likely to have affected both the composition and diversity of small mammal communities living in agricultural landscapes. In this context, we compared population abundance (expressed as an index of relative abundance), species richness (S), and species diversity (expressed as Shannon and Pielou indexes) of small mammal assemblages (i.e. sub-sets of the entire small mammal community) living in three areas in North-East Italy positioned along a gradient of agricultural land-use intensification (measured with the Landscape Conservation Index). We expected that assemblages would be less diverse and dominated by generalist species where the landscape was more intensely cultivated and where semi-natural habitats were less common. In the three areas, from a total of 4630 trap-nights, 668 individuals were captured with Sherman traps, belonging to four species (Apodemus agrarius, A. flavicollis, A. sylvaticus and Microtus arvalis). The results showed that population abundance, type of species present (but not species richness), and species diversity were affected by agricultural intensification and landscape naturalness. In particular, moving from less natural to more natural landscapes, we observed no effect on richness of species but increasing diversity due to a greater abundance of the more specialist species, such as A. agrarius and, partially, A. flavicollis, the latter only present in the most natural area. Generalist species, namely A. sylvaticus, and those associated with disturbed environments, such as M. arvalis, were instead more abundant in less natural landscapes. When considering population abundance, the highest overall abundance of small mammals was found in the most disturbed landscape. The results were consistent with those of research carried out in other agroecosystems of Europe and highlight the controversial effect of the anthropogenic impact on small ...